Revitalizing Tradition Through Cultural Festivals: An Effort To Enhance Local Tourism - Sahar, Santri (PT. Anagata Sembagi Education, 2024)
Revitalizing traditions through the organization of cultural festivals is a strategic step to strengthen local cultural identity while improving the tourism sector. This article explores the role of cultural festivals in promoting local traditions as sustainable tourist attractions, focusing on some examples of cultural festivals in Indonesia. Through a qualitative approach and case study method, this study examines the impact of cultural festivals on local tourism and how they contribute to the preservation of traditions, the formation of collective identity, and the improvement of the community's economy. The findings of the study show that cultural festivals can strengthen the sense of belonging to local traditions among the community, introduce cultural values to the younger generation, and attract domestic and foreign tourists. In addition, cultural festivals have proven to have a significant economic impact on the local population through business and employment opportunities. Based on the results of the research, support from the government, business actors, and the community is very important to ensure the sustainability of cultural festivals as one of the strategies for developing culture-based local tourism